Exploring SMEs' qualitative growth and networking through formalization. Issue 4 (19th May 2020) - Milanesi, Matilde; Guercini, Simone; Tunisini, Annalisa
Abstract : Purpose: This paper aims to analyze the role of networking through formalization, namely, the adoption of specific contractual forms, in triggering small- and medium-sized enterprises (SMEs') qualitative growth. The paper adopts an approach to SMEs' growth that stresses the multi-dimensionality nature of the concept, which includes not only size but also relationship and capability growth. Design/methodology/approach: A qualitative methodology is used, based on the study of cases of SMEs from an Italian fashion district, connected by a specific contractual form – the so-called "network contract" (NC) – promoted by the national government. Two cases of NCs are presented, a vertical and a horizontal network. Findings: The paper highlighted the positive influence of NCs, intended as a managerial strategy not only aimed at collaboration, on the growth paths of SMEs but also stressed that the influence of NCs cannot be isolated, but acts virtuously together with other variables. Such variables include entrepreneurs' and managers' individual traits, the context – industrial district in the two cases under study – in which SMEs operate, the presence of an external actor that stimulates the adoption of NCs. Originality/value: The focus on qualitative growth, which can be triggered by the formalization of business relationships through contractual forms, contributes to the debate on the nature and content of SMEs' growth. The awareness of the variables that contribute to SMEs' growth is crucial for both entrepreneurs and institutional actors who want to create the conditions to undertake paths of qualitative growth.